(untitled) (مجلة البحوث الأكاديمية, 2019)
It is well established that people learn differently from one another and there has been considerable research into how these differences can be characterised. The work by Honey and Mumford is widely recognised and proposes 4 learning styles, Activist, Pragmatist, Theorist and Reflector. Adaptive hypermedia systems have been used to allow various types of learning material, related to the different stages of the Kolb learning cycle, to be presented to students with different learning styles in different orders. Work being undertaken at The College Of Computer Technology Tripoli is designed to evaluate the effectiveness of this approach. E-learning material to support various different learning activities has been created for a first year undergraduate course on computer technology. The activities have been designed to match the learning styles identified by [1,2]. The material has been presented to different groups of students with the activities in different sequences. The students were later tested to establish their learning style and where the learning style matched the delivery order, students reported that they had made better progress than those students for whom there was a mismatch. Further work is planned to verify this preliminary finding by investigating whether an objective measure of the students’ achievement matches their perceptions.